2019
DOI: 10.1371/journal.pone.0221749
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethyl alcohol on the severity of injuries in fatal pedestrian victims of traffic crashes

Abstract: Introduction A substantial percentage of traffic crashes involve people under the influence of ethyl alcohol. In such circumstances, we speak of the possible effect of ethanol upon trauma outcomes. The present research aimed to assess the state of sobriety fatal pedestrian victims and the correlation between the level of sobriety and the severity of injuries. Research material and method The data was obtained from the Warsaw Medical University's Department of Forensic Medicine. The analysis covered the data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…However, the analyses using hospital length of stay and ISS are broadly similar. Lastly, we cannot rule out the possibility of residual confounding, such as the effect of alcohol [ 36 , 37 ], despite our best attempts to collect and control for various factors including socioeconomic and injury related factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analyses using hospital length of stay and ISS are broadly similar. Lastly, we cannot rule out the possibility of residual confounding, such as the effect of alcohol [ 36 , 37 ], despite our best attempts to collect and control for various factors including socioeconomic and injury related factors.…”
Section: Discussionmentioning
confidence: 99%
“…According to legal standards in Poland, when the blood alcohol content is or nears a concentration of 0.2% to 0.5% (or the presence of 0.1 mg to 0.25 mg of alcohol in 1 dm 3 in exhaled air), this is considered a state after alcohol consumption [22]. When the blood alcohol level is or nears a blood alcohol level above 0.5% (and there is more than 0.25 mg in 1 dm 3 in the exhaled air), we are talking about a state of intoxication [29][30][31][32]. Unfortunately, in the presented analysis, the above-mentioned limits were significantly exceeded in pedestrians (0.2-4.40% ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Lasota et al on the impact of ethanol on the severity of injuries in fatal road traffic accidents involving pedestrian victims, demonstrated that the effect of ethanol on injury severity cannot be mentioned without taking into account the gender and age of the victims [6,7].…”
Section: Methodsmentioning
confidence: 99%